2002
DOI: 10.1073/pnas.072346699
|View full text |Cite
|
Sign up to set email alerts
|

Renewable and nonrenewable resources: Amino acid turnover and allocation to reproduction in Lepidoptera

Abstract: The allocation of nutritional resources to reproduction in animals is a complex process of great evolutionary significance. We use compound-specific stable isotope analysis of carbon (GC͞combus-tion͞isotope ratio MS) to investigate the dietary sources of egg amino acids in a nectar-feeding hawkmoth. Previous work suggests that the nutrients used in egg manufacture fall into two classes: those that are increasingly synthesized from adult dietary sugar over a female's lifetime (renewable resources), and those th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
299
2
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(317 citation statements)
references
References 31 publications
11
299
2
5
Order By: Relevance
“…Although we are aware of adult nectar feeding in Lepidoptera (Nelson 1936), the experimental rationale we adopted was intended to determine whether there were isotopic differences between the populations that could be used as markers. We suggest that adult nectar feeding would contribute little to the overall isotope signature of the moth as it is quickly used as an available energy source for flight (O'Brien et al 2002). In previous work we have shown that insects fed sugar ad libitum turn over about 50% of their total body C throughout their life time and that about 50% is structural and has minimal turnover (Hood-Nowotny et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we are aware of adult nectar feeding in Lepidoptera (Nelson 1936), the experimental rationale we adopted was intended to determine whether there were isotopic differences between the populations that could be used as markers. We suggest that adult nectar feeding would contribute little to the overall isotope signature of the moth as it is quickly used as an available energy source for flight (O'Brien et al 2002). In previous work we have shown that insects fed sugar ad libitum turn over about 50% of their total body C throughout their life time and that about 50% is structural and has minimal turnover (Hood-Nowotny et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…From this we assume that chitin-dominant tissues such as wings or front leg tibiae, are chitin rich structures, which will turnover slowly thus retaining their natal isotopic signature. The sugar-rich nectar diet of most moths provides only trace amounts of amino acids and these do not appear to contribute to adult N (O'Brien et al 2002). Moreover studies of N assimilation in adult Lepidoptera have shown minimal N uptake (MolleMan et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both differences were statistically significant (t-tests: t ¼ 3.94, P ¼ 0.0043 for d 18 O and t ¼ 9.43, P < 0.0001 for dD, both with df ¼ 8). We calculate the contribution of oxygen and hydrogen from drinking water to hair in residents using the following mixing expression: 18,45 % hair oxygen from drinking water ¼ ðd 18 We note that the use of this expression assumes that other sources of hair oxygen in these populations (e.g. diet, atmospheric O 2 ) do not differ isotopically between locations, nor do their fractional contributions of oxygen to hair.…”
Section: Stable Oxygen and Hydrogen Isotope Composition Of Hair From mentioning
confidence: 99%
“…The evolution of new life histories is expected to require changes in the relative flux through these pathways, for example, when relative somatic versus reproductive effort is altered during the course of adaptation. Although variation in amino acid acquisition from the diet has been investigated in ecological studies of interspecific life-history trade-offs (Boggs 1997a(Boggs , 1997bO'Brien et al 2002O'Brien et al , 2005, to our knowledge, no study has investigated genetic modifications in amino acid metabolism that contribute to within-species variation in life-history specialization.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of new life histories is expected to require changes in the relative flux through these pathways, for example, when relative somatic versus reproductive effort is altered during the course of adaptation. Although variation in amino acid acquisition from the diet has been investigated in ecological studies of interspecific life-history trade-offs (Boggs 1997a(Boggs , 1997bO'Brien et al 2002O'Brien et al , 2005, to our knowledge, no study has investigated genetic modifications in amino acid metabolism that contribute to within-species variation in life-history specialization.Wing polymorphism in insects is a powerful experimental model that has been used extensively to investigate the physiological, and more recently, the biochemical basis of life-history evolution (Zera and Denno 1997;Zera et al , 1998Zera and Harshman 2001; Zhao and Zera 2002;Zera andZhao 2003a, 2004). Gryllus firmus, the most intensively studied species in this regard, exists in natural populations as two genetically specified morphs.…”
mentioning
confidence: 99%